KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA : Studi kasus di SMP Santo Fransiskus Asisi Sungai Pinyuh - Inviolata, Inviolata; Usman Radiana; Halida; Maria Ulfah; Alfandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the Transformational Leadership of the Principal in Implementing the Strengthening of Pancasila Student Profile Project at SMP Santo Fransiskus Asisi Sungai Pinyuh. The research adopts a qualitative approach. The study participants consist of 10 individuals, including 3 males and 7 females, selected using purposive sampling criteria. The participants include the principal, vice principals for curriculum and student affairs, administrative staff, teachers, and students aged 13–55 years. This descriptive research employs observation, interviews, and documentation techniques. The data collection instruments include observation guidelines, interview protocols, and document analysis. The data analysis process involves three stages: data collection, data reduction, and conclusion drawing. The main findings of this study indicate that the principal implements transformational leadership through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The primary challenges faced include human resource readiness, limited facilities and infrastructure, and a lack of support from parents and external parties.The strategies to overcome these challenges include enhancing teacher capacity through training and mentoring, optimizing local resources, increasing student motivation through appreciation and personalized approaches, and strengthening communication with parents and the community. In conclusion, the effective implementation of transformational leadership supports the execution of the Strengthening of Pancasila Student Profile Project, although additional support from all stakeholders is required. The implications of this study contribute to the body of knowledge on transformational school leadership, particularly in the implementation of the Strengthening of Pancasila Student Profile Project, as well as the challenges and strategies involved in its implementation.